Evaluation of the physical properties and stability of two lipid drug delivery systems containing mefloquine - Slabbert, C.; Plessis, L.H. du; Kotzé, A.F. (International journal of pharmaceutics, 2011)
Stability data is used to determine the change the product has undergone over a certain time period at specific temperatures. In the present study, the physical stability characterized by size, pH and entrapment efficacy of mefloquine loaded liposomes and Pheroid™ vesicles were investigated. Size was accurately determined by flow cytometry. Entrapment efficacy, after unentrapped drug was removed was successfully determined by UV-spectrophotometry. The formulations contained 0.5% (m/v) mefloquine and results showed that mefloquine interfered with the formation of lipid bilayer of the liposomes. Liposomes increased in size from 5.22 ± 0.03 μm to 9.71 ± 1.11 μm with accelerated stability and large aggregates were observed. A notable difference in stability testing of Pheroid™ vesicles was seen with no significant increase in size. Entrapment efficacy of 68.72 ± 0.04% (5 °C), 67.45 ± 2.92% (25 °C) and 67.45 ± 2.92% (30 °C) were obtained at the different storage conditions. With these findings the mefloquine loaded Pheroid™ vesicles are stable and should be used investigated for the possible increase in efficacy and bioavailability and decrease toxicity.